Sosialisasi Pengoperasian, Uji Fungsi Dan Pemeliharaan Alat Cardiotocograph (Ctg) - D*, Hotromasari; Sijabat, Salomo; Adiansyah, Adiansyah (Jurnal Abdimas Mutiara, 2022)
Cardiotocography (CTG) is a tool used by obstetricians to monitor heart rate and uterine contractions while the baby is in the womb. Babies in the womb have a heart rate between 110 and 160 beats per minute and increases when the baby moves. The operation of medical equipment is very important to be known by the user in accordance with standard operating procedures for the use of medical equipment. Standard operating procedures are a standardized workflow/method. Operational Standards serve as a reference guide for the use of equipment. The use of cardiotocography must follow the Standard Operating Procedures. Functional test is an overall test through testing the parts of the Medical Device with maximum capability without actual load, so that it can be seen whether the whole Medical Device can be operated properly according to the specifications of the equipment. Dissemination of Operation, Function Test and Maintenance of Cardiotodography Equipment (Ctg) aims to increase knowledge and insight for users in hospitals and train users in the operation of Cardiotodography equipment. In order to avoid errors in the use of equipment. Cardiotocography has several parameters, namely Oxygen Saturation in the blood (SPO2), Blood Pressure (NIBP), Electrocardiograph (EKG), Toco Transducer, UC Transducer, and fetal movement markers. Each parameter has a different function to view the patient's diagnosis. Good and focused maintenance of medical equipment and carried out in a planned, organized, and systematically actualized manner in accordance with procedures.